2010
DOI: 10.1007/s10409-010-0365-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing dynamic response of multispan viscoelastic thin beams under a moving mass via generalized moving least square method

Abstract: Dynamic response of multispan viscoelastic thin beams subjected to a moving mass is studied by an efficient numerical method in some detail. To this end, the unknown parameters of the problem are discretized in spatial domain using generalized moving least square method (GMLSM) and then, discrete equations of motion based on Lagrange's equation are obtained. Maximum deflection and bending moments are considered as the important design parameters. The design parameter spectra in terms of mass weight and velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…For interpolation, several powerful methods exist such as generalized moving least square method [4,26,27], in which coefficients of basis functions vary on each data point in order to interpolate local values. On the other hand, reconstruction aims to find systems that globally hold, and one can obtain relations between variables including their degree and coefficients from the results.…”
Section: Using the Order Ideal To Create A Reduced Projection Of Polymentioning
confidence: 99%
“…For interpolation, several powerful methods exist such as generalized moving least square method [4,26,27], in which coefficients of basis functions vary on each data point in order to interpolate local values. On the other hand, reconstruction aims to find systems that globally hold, and one can obtain relations between variables including their degree and coefficients from the results.…”
Section: Using the Order Ideal To Create A Reduced Projection Of Polymentioning
confidence: 99%
“…According to the inherent complexities of the moving mass problems in the linear beams, some studies have been carried out using different numerical schemes, e.g., [5][6][7][8][9][10]. As a nonlinear moving mass problem, Xu et al [11] derived the nonlinear equations of motion for a finite elastic beam traversed by a moving mass.…”
Section: Introductionmentioning
confidence: 99%
“…ey demonstrated the efficiency and simplicity of their method using several numerical examples. Kiani et al [21,22] reported a numerical parametric investigation into the design parameters of multispan viscoelastic shear deformable beams subjected to a moving mass via the generalized moving least squares method and another comprehensive parametric investigation on the evaluation of design parameters, where the maximum deflection and bending moment of beams were analyzed. Regarding the problem of moving loads acting on thin beams with geometric nonlinearity, they also employed an efficient meshless method and the reproducing kernel particle method for a spatial discretization nonlinear beam [23].…”
Section: Introductionmentioning
confidence: 99%